ANALISIS KESULITAN BELAJAR SISWA KELAS V DALAM PEMBELAJARAN TEMATIK DI SD NEGERI 238/VI TANJUNG PUTUS II - Dodi Widia Nanda; Eka Filahanasari; Rodiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to analyze students' learning difficulties in thematic learning at SD Negeri 238/VI Tanjung Putus. Problems are often found in thematic learning. This research method uses qualitative research methods. The time and location of the research were at the 238/VI Tanjung Putus II Public Elementary School located on Jalan Raya Muara Kibul Km 27, Rt 01/00, Tabir Barat District, Merangin Regency, Jambi Province-Indonesia. Primary data source. Techniques in collecting data are interviews, observation, and documentation. Test the validity of this research data using a credibility test. Data analysis techniques used are data collection, data reduction, data presentation (data display) and drawing conclusions. The results of this research are that there are still many students who find it difficult to interpret what is felt, heard and observed; students are less attentive and less focused on learning. There are too many useless activities that make it difficult to remember teaching materials. Students are slow in processing something. Low student academic achievement. Difficulty generates new understanding. students who have learning difficulties show inappropriate behavior. There are 2 factors that cause students to experience learning difficulties, namely internal and external factors. Such as the lack of students' attention to the subject matter, the lack of participation and response of students when participating in teaching and learning activities, the slowness of students in understanding the material, incomplete test scores, the influence of friends in the community who always play, the influence of friends who are around where they live.